Adverse events following vaccination with an inactivated, Vero cell culture-derived Japanese encephalitis vaccine in the United States, 2009–2012. Issue 5 (29th January 2015) - Rabe, Ingrid B.; Miller, Elaine R.; Fischer, Marc; Hills, Susan L.
Highlights Vero cell culture-derived Japanese encephalitis vaccine (JE-VC) was licensed in the US in 2009. We reviewed adverse events reported in the U.S. for the first 3 years post-licensure. Of 42 reported adverse events, 5 (12%) were classified as serious for a reporting rate of 1.8 per 100, 000 doses distributed; there were no deaths. These data suggest a good safety profile for JE-VC. Post-licensure surveillance may detect rare adverse events and safety data should continue to be monitored.